2020
DOI: 10.1002/ijc.33153
|View full text |Cite
|
Sign up to set email alerts
|

Childhood cancer incidence among specific Asian and Pacific Islander populations in the United States

Abstract: Despite the vast genetic and environmental diversity in Asia, individuals of Asian and Pacific Islander (API) descent are often combined into a single group for epidemiologic analyses within the U.S. We used the Surveillance, Epidemiology and End Results (SEER) Detailed Asian/Pacific Islander Database to calculate incidence rates for discrete groups among children aged 0 to 19 years. Due to sample size constraints we pooled incidence among regional groups based on countries of origin: East Asians (Chinese, Jap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…We grouped broad racial and ethnic categories together, although recent reports have shown that incidence may vary within subpopulations of these large and diverse groups. 51 As noted above, although we presented unadjusted IRR estimates, these map closely to the odds ratios observed in previous work, which were adjusted for socioeconomic status proxies and known perinatal risk factors, 3 suggesting that unmeasured confounding is not likely to be a major driver of these observations. Last, we were unable to look at race-and ethnicity-specific trends by tumor subtype, such as ALL cytogenetic subtypes or solid tumor histologic subtypes, which should be explored in more detailed data sets.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…We grouped broad racial and ethnic categories together, although recent reports have shown that incidence may vary within subpopulations of these large and diverse groups. 51 As noted above, although we presented unadjusted IRR estimates, these map closely to the odds ratios observed in previous work, which were adjusted for socioeconomic status proxies and known perinatal risk factors, 3 suggesting that unmeasured confounding is not likely to be a major driver of these observations. Last, we were unable to look at race-and ethnicity-specific trends by tumor subtype, such as ALL cytogenetic subtypes or solid tumor histologic subtypes, which should be explored in more detailed data sets.…”
Section: Discussionsupporting
confidence: 71%
“…Additionally, we did not have sufficient numbers of cases in the minority racial and ethnic groups to examine trends by single year of age. We grouped broad racial and ethnic categories together, although recent reports have shown that incidence may vary within subpopulations of these large and diverse groups 51 . As noted above, although we presented unadjusted IRR estimates, these map closely to the odds ratios observed in previous work, which were adjusted for socioeconomic status proxies and known perinatal risk factors, 3 suggesting that unmeasured confounding is not likely to be a major driver of these observations.…”
Section: Discussionmentioning
confidence: 74%
“…Notably, the North American regions with Mexican, Canadian, and American populations display high incidence rates of AL (31.4–65.4) in comparison to other populations ( 2 , 3 , 8 – 10 , 72 , 78 – 81 ). Furthermore, studies in children of Hispanic ancestry, aged 0–19 years, have also shown incidence rates that are among the highest worldwide ( 7 , 11 , 82 – 89 ) ( Supplementary Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…This disparity in ALL risk corresponds to what has been observed geographically. For instance, Latin American countries, including Mexico and Costa Rica, have some of the highest incidences of childhood ALL in the world [91,92] . Meanwhile, the highest incidence of childhood ALL in the United States is found in the West United States Census Region, where a high proportion of residents are Hispanics/Latinos [65] .…”
Section: Incidence Of All Is Highest In Hispanics/latinosmentioning
confidence: 99%